1981
DOI: 10.2355/isijinternational1966.21.518
|View full text |Cite
|
Sign up to set email alerts
|

Coal Blending Theory-Retrospect and Prospect

Abstract: SynopsisThis paper summarizes a series of experimental studies conducted by the author et al., on coal blending theory which is a basic condition for the production of coke. A brief history is given of the condition of coking coal supply and past studies undertaken in Japan ranging from the establishment of basic concepts of coal blending in the period immediately after World War II to recent trends in the search for blending standards aiming at the improvement of hot properties of coke. The essential point in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…[1][2][3] In particular, Gieseler plastometer method and dilatometer test standardized by JIS M8801 have long been used for measuring the caking properties and finally controlling coke strength. [4][5][6] For example, Miyazu et al shows that Gieseler maximum fluidity (MF) of coal blend should be more than 200 ddpm to make high strength coke.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] In particular, Gieseler plastometer method and dilatometer test standardized by JIS M8801 have long been used for measuring the caking properties and finally controlling coke strength. [4][5][6] For example, Miyazu et al shows that Gieseler maximum fluidity (MF) of coal blend should be more than 200 ddpm to make high strength coke.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In particular, Gieseler plastometer method and dilatometer test standardized by JIS M8801 have long been used for measuring the caking properties and finally controlling coke strength. [4][5][6] For example, Miyazu et al shows that Gieseler maximum fluidity (MF) of coal blend should be more than 200 ddpm to make high strength coke. 4) However, the effect of excessive MF on coke strength has not been clarified because high fluidity coal is thought to act as a binder in a coal blend to produce high strength coke while high fluidity coal produces highly-porous structure which leads fragile coke in case that the coal alone is carbonized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because higher MF means basically greater caking property. 4) In addition, it was reported that shorter maximum permeation distance in same MF levels becomes higher coke strength. 2) Therefore, maintaining MF and reduction of maximum permeation distance of coal should be the most ideal upgrading by weathering processing.…”
Section: Test2mentioning
confidence: 99%
“…Maximum fluidity (MF), which is measured by Gieseler plastometer method (conventional method, JIS M 8801 3) ) has been widely used as a caking index in cokemaking industry. 4) However, it has been pointed out that the conventional method has some problems in the measurement 5) and MF rarely has unclear relationship with coke strength. 6) In our previous study, 2) a new measurement method named as "permeation distance method" was developed in order to overcome the problems of conventional method and supplement the conventional evaluation of coal thermoplasticity.…”
Section: (Received On December 3 2018; Accepted On February 15 2019)mentioning
confidence: 99%